Replication protein A modulates its interface with the primed DNA template during RNA–DNA primer elongation in replicating SV40 chromosomes - Mass, Gilad (Oxford University Press, 2001)
The eukaryal single-stranded DNA binding protein replication protein A (RPA) binds short oligonucleotides with high affinity but exhibits low cooperativity in binding longer templates, opposite to prokaryal counterparts. This discrepancy could reflect the smaller size of the replicative template portion availed to RPA. According to current models, this portion accommodates an RNA–DNA primer (RDP) of <40 nt (nested discontinuity) or a several-fold longer Okazaki fragment (initiation zone). Previous in situ UV-crosslinking revealed that RPA also interacts with nascent DNA, especially growing RDPs. Here we compare nascent SV40 DNA chains UV-crosslinked to the middle and large RPA subunits and use the data to re-examine the two models. The middle subunit interacted with the nascent chains after a few DNA residues were added to the RNA primer while the large subunit became accessible after extension by several more. Upon RDP maturation, the middle subunit disengaged while the large subunit remained accessible during further limited extension. A corresponding shift in preference in favor of the large subunit has been reported for purified RPA and synthetic gapped duplexes upon reduction of the gap from 19 to 9 nt. Combined, these facts support the proposal that the mature RDP faces downstream a correspondingly small gap, possibly created by removal of the RNA primer moiety from an adjacent, previously synthesized RDP (nested discontinuity) but insufficient for continuous elongation of the RDP into an Okazaki fragment (initiation zone).